Peran Gaya Kepemimpinan dan Budaya Organisasi dengan Kinerja Karyawan di CV. Zinnia Indonesia - Nur Apriyani; Aldy Santo Hegiarto (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The purpose of this study was to see the impact of leadership style and organizational culture on employee performance at CV.Zinnia Indonesia. The informants used in this study were 3 informants who met the criteria. The results of the study outline that leadership style and organizational culture have a significant impact on employee performance. The leadership style and organizational culture that exists at CV. Zinnia Indonesia is not efficient enough to improve employee performance. With the findings in this study, the leadership style and organizational culture at CV. Zinnia Indonesia to make company policies that can maintain indicators of the role of leadership style and organizational culture.